ANALYSIS OF THE BEHAVIOUR OF VISITORS TO MUNICIPAL WEBSITES AND SOCIAL NETWORK ACCOUNTS - Malinovska, Laura; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
Nowadays, when services of municipalities are available only remote, need for reliable information is constantly increasing- starting with administration office contacts and ending with current COVID-19 restrictions. This flow of information in Latvia is provided by websites and social media accounts of local municipalities. The author's work has explored statistics and user behaviour data of foreign municipalities websites during COVID-19 pandemic. Furthermore an survey for Latvia’s municipalities was conducted to find out how COVID-19 pandemic has changed user behaviour and website statistics. As a result, author of the work compared data obtained from surveys and examinated available data from foreign municipalities, which could be used facing further crisis situations.